A regulatory assessment of the Build-Own-Operate model for New Nuclear Build in South Africa - Essa, Fagmie (Department of Mechanical Engineering, 2018)
Governments pursue New Nuclear Build (NNB) projects for different strategic reasons. Many countries are not able to devise a funding model for the excessive costs of a NNB project nor do they have the local skills to construct, operate and maintain a NPP. South Africa's Integrated Resource Plan 2016 indicates that the base case scenario includes a target date of 2037 for the first unit of a NNB programme. This date moves to 2026 when the carbon budget is included in the forecast. The National Nuclear Regulator (NNR) has limited experience in licensing NNB programs as the country's only other commercially operating nuclear power plant was completed in 1984. The Build-Own-Operate (BOO) model is being promoted by Russia as an option to finance, design, supply most of the equipment for, construct and operate, a NPP. The first of this model is being executed at Akkuyu in Turkey. South Africa and specifically the NNR will face many challenges should it pursue the Build-Own- Operate model for its New Nuclear Build programme, given this model's novel and complex demands. This study has concluded that the Nuclear Energy Policy does not support an entity other than Eskom (the South African electricity utility) from owning and operating any new NPP in South Africa. The NNR does not presently have the resources to be able to service a NBB program but should be able to adapt to the increased demands of a NNB programme. The minister responsible for the promotion of nuclear energy also provides oversight of the NNR. This conflict of interest does not appear to have affected NNR decisions thus far; however, a NNB programme will exert undue pressure on all stakeholders which could change the relationship between the NNR and its minister. The National Nuclear Regulator Act (NNRA) needs to be enhanced to change this reporting structure while also enhancing the independence of the NNR. Should the Hinkley Point C model be followed in South Africa, the appointment of a design authority within the licensee which effectively creates an additional layer of verification should warrant strong consideration for the South African NNB model. The Akkuyu BOO model challenges the principles of the Intelligent Customer concept. Should the Akkuyu BOO model be followed, the NNR would require the licensee to show that independent verification is in place. Roles and responsibilities should be clearly described and understood by all stakeholders. The onus remains with the licensee to prove Intelligent Customer capability.